THE USE OF SEQUENCES OF PICTURES IN TEACHING NARRATIVE TEXT TO IMPROVE STUDENTS' WRITING ABILITY (A Quasi Experimental Research in the Eighth Grade Students of a State Junior High School in Bandung) - Dena Astriyanti, - (2011)
The research entitled The Use of Sequences of Pictures in Teaching Narrative Text to Improve Students' Writing Ability is to investigate whether or not sequences of pictures are effective in teaching narrative text. It also aims to find out students' responses toward the use of sequences of pictures in teaching writing narrative text. The research was conducted in a State Junior High School in Bandung. The research employs quasi experimental with pre test and post test design. After conducting some treatments, the data collected through pre test and post test were analyzed by using SPSS 16.0 for windows. The research proposes null hypothesis. The data analysis of independent t-test shows that there is significance difference between post test means for both control group and experimental group. Therefore, it can be stated that the use of sequences of pictures is considered effective in teaching narrative text and has different result in improving students' writing ability. Furthermore, the result of interview indicates the students' positive responses toward the use of sequences of pictures in narrative writing lesson. The research findings show that the use of sequences of pictures can give positive effects to the students particularly in writing a narrative text. Moreover, there are some factors in improvement student's writing results when using sequences of pictures in writing narrative text. The first one is related to student's interest and motivation to engage in writing activity, while the second factor is the technique and media used in presenting the material. However, other writing researches are needed to enhance this research. Therefore, it is recommended that other researcher conduct more comprehensive research to employ sequences of pictures in writing lesson.